Dampak Pandemi COVID-19 Terhadap Loyalitas Pelanggan pada Beverage Shop di Onezo Indonesia - Stephanie Rosanto; Novy Ratna Sari (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2021)
The food and beverage (F&B) industry is one of the sectors affected by the COVID-19 pandemic. The prohibition of large-scale social interactions in the community, such as holding gatherings during the Large-Scale Social Restrictions (Pembatasan Sosial Berskala Besar / PSBB) period established by each region, has also contributed to the sharp decline in food and beverage sales. The total average result of the COVID-19 Pandemic Impact (X) variable questionnaire in OneZo Indonesia is 67% which is in the good category. Of all the statement indicators, it can be seen that the lowest indicator is "Does the pandemic affect your income" with a result of 48%, which can be seen from the general description of OneZo Indonesia's customer respondents who are mostly private employees. The average result of the total Customer Loyalty (Y) questionnaire at OneZo Indonesia is 64% which is in the good category. Of all the indicators, there is one indicator that has the smallest value, namely "Customers have the desire to recommend OneZo Indonesia to others". From the results of observations and interviews conducted, this is due to several factors, one of which is the price of the products offered by OneZo Indonesia which are in the middle to upper category and OneZo Indonesia outlets are still not evenly distributed, there are only a few in the city center. big. From the results of simple linear regression analysis, it was found that the impact of the COVID-19 pandemic variable X had no effect on customer loyalty OneZo Indonesia variable Y.